Rethinking Teaching Strategies in Digital Environments to Foster Critical Thinking and Innovation Skills - Liam Christopheer Johnson (Nusantara Education, 2025)
The rapid advancement of digital technologies has transformed educational landscapes, necessitating a reevaluation of teaching strategies to cultivate essential 21st-century skills. This study explores how teaching strategies in digital environments can be reimagined to enhance students’ critical thinking and innovation skills. The primary objectives are to identify effective pedagogical approaches that foster higher-order cognitive abilities, analyse the role of digital tools in supporting innovative learning, and propose a framework for integrating critical thinking and creativity into digital instruction. This study employs a qualitative field-based approach, with data collected through interviews, observations, and documentation involving 120 educators and 450 students across higher education institutions. The data were analysed using thematic analysis to identify patterns in teaching practices, challenges, and learning outcomes. Findings indicate that active learning strategies, such as problem-based learning, collaborative projects, and gamified simulations, significantly enhance students’ critical thinking and innovation skills when mediated by digital platforms. Interactive tools, including virtual labs, collaborative software, and AI-driven learning environments, were shown to support experimentation, reflective thinking, and creative problem-solving. Educators emphasised the need for adaptive teaching approaches, continuous feedback, and scaffolding to maximise learning outcomes in digital contexts. This study contributes to the scholarly discourse by providing empirical evidence on the integration of critical thinking and innovation into digital pedagogy and offering a practical framework that can guide educators in designing transformative learning experiences. By bridging theoretical insights and practical strategies, the research informs curriculum development, instructional design, and policy-making aimed at equipping learners with the competencies required for complex, technology-driven societies.